Sit in the Sun And Other Lessons in the Spiritual Wisdom of Cats. - Sweeney, Jon M. (1517 Media, 2023)
Our greatest spiritual teachers may just be the furry companions right in our own homes--the cats we love and treasure. They live in the present moment, approach life with playfulness, sit in the sun, and know how to trust others. From the author of The Pope's Cat comes a warm, delightful book with lessons from our nearest spiritual companions.